Surface plasmon resonance sensor to detect n-hexane in palm kernel oil using polypyrrole nanoparticles reduced graphene oxide layer - Sadrolhosseini, Amir Reza; Habibiasr, Mina; Soleimani, Hassan; Hamidon, Mohd Nizar; Yap, Wing Fen; Lim, H. N. (Hindawi, 2021)
Palm kernel oil was extracted using n-hexane. Rotary evaporator and oven were used to remove n-hexane from the oil. Measurement of n-hexane in low concentration is significant and interest subject. In this study, the concentration of n-hexane was measured using the surface plasmon resonance technique. In order to improve the sensitivity of surface plasmon resonance sensor, the polypyrrole nanoparticles decorated reduced graphene oxide (sensing layer) was prepared using the electrodeposition technique on the surface of gold film. Different concentration of n-hexane in isooctane and the palm kernel oil before and after purification was tested using sensing layer. The sensor limit was about 1 ppm. The results were matched with the gas chromatography results. The thickness and roughness of sensing layer were increased after the interaction with n-hexane which was obtained from atomic force microscopy.